Factors predicting influenza vaccination adherence among patients in dialysis: an Italian survey. Issue 10 (3rd October 2019) - Battistella, Claudio; Quattrin, Rosanna; Celotto, Daniele; d'Angelo, Matteo; Fabbro, Elisa; Brusaferro, Silvio; Agodi, Antonella; Astengo, Matteo; Baldo, Vincenzo; Baldovin, Tatjana; Bert, Fabrizio; Biancone, Luigi; et al.
ABSTRACT: Introduction : The aim of this study was to investigate knowledge and practices about influenza among patients on dialysis services of Italian hospitals at risk of severe influenza infection and vaccine and to identify predictive factors to vaccination adherence. Methods : A cross-sectional observational study was carried out from January 2017 to July 2017 after the 2016/2017 influenza vaccination campaign. The questionnaire was administered to all patients treated in seven large Italian dialysis services. It consisted of influenza vaccination coverage, knowledge about influenza and its vaccination, perceived risk of influenza complications, recommendations on influenza uptake received by general practitioner (GP) and nephrologist. Results : Response rate was 90% (703/781). Patients' knowledge about influenza infection and vaccine were detected by nine closed questions: 35.6% of responders answered correctly to ≥ 6 sentences, 47.5% of them reported that "influenza vaccine can cause influenza" and 45.7% believed that "antibiotics are a correct strategy to treat influenza". Levels of perceived risks of hospitalisation and death were low in 39.3% and 16.5% of patients respectively. The adherence to the last seasonal influenza vaccination was 57.5%. The multivariate predictors of influenza vaccination uptake resulted: age ≥65, male, consulting TV/radio, asking information to GP and/or nephrologist. Conclusions : The study reveals the low adherence to influenza vaccination and the subotpimal level of knowledge in dialysis patients. Different strategies, including a greater alliance among nephrologists and GPs to prevent influenza should be encouraged to improve the adherence to influenza vaccination in this at risk group.